Classics in Migration - Introduction. (7th June 2019) - Cohen, Robin
Abstract: As the publication of this journal itself indicates, Migration Studies has entered the mainstream of academic life, particularly in the social sciences. This was by no means always the case. Migration matters were covered, often casually, in human geography, history, statistics, demography and sociology and, under the rubric of labour markets, in economics. However, stand-alone courses, let alone Masters' degrees in migration, were unknown until a couple of decades ago. Does this new-found recognition of Migration Studies mean that it is an incipient discipline, or should it be more modestly characterized as a field, or simply a preoccupation driven by current political concerns?